2020
DOI: 10.2807/1560-7917.es.2020.25.48.2000895
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors associated with severe COVID-19: prospective analysis of 1,045 hospitalised cases in North-Eastern France, March 2020

Abstract: Background In March 2020, the COVID-19 outbreak was declared a pandemic by the World Health Organization. Aim Our objective was to identify risk factors predictive of severe disease and death in France. Methods In this prospective cohort study, we included patients ≥ 18 years old with confirmed COVID-19, hospitalised in Strasbourg and Mulhouse hospitals (Fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
65
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 28 publications
11
65
2
2
Order By: Relevance
“…Another multicenter study in Spain and Andorra [26] of 960 patients reported a mortality rate of 31% (203). Another multicenter prospective study in France [27] of 335 critically ill patients reported a mortality rate of 7.76% (26). In a single-center study in Sweden of 260 participants, mortality was found in 60 of those admitted to the ICU [28].…”
Section: Plos Onementioning
confidence: 96%
“…Another multicenter study in Spain and Andorra [26] of 960 patients reported a mortality rate of 31% (203). Another multicenter prospective study in France [27] of 335 critically ill patients reported a mortality rate of 7.76% (26). In a single-center study in Sweden of 260 participants, mortality was found in 60 of those admitted to the ICU [28].…”
Section: Plos Onementioning
confidence: 96%
“…In a retrospective study, dyspnea and tightness in the chest were much more common in deceased patients (Chen et al, 2020). Moreover, it was one of the associated predictors of severe disease and death (Kaeuffer et al, 2020).…”
mentioning
confidence: 98%
“…Dyspnea is the main experience related to the avoidance of survival threats; it is a multidimensional construct of breathing sensations with qualitative, quantitative, and descriptive components (Abernethy and Wheeler, 2008;Parshall et al, 2012;Kaeuffer et al, 2020). The pathophysiological mechanisms, rather than pain, are complex and can coexist (Nishino, 2011).…”
mentioning
confidence: 99%
“…Several reports from retrospective cohort studies in France 13 and China 14 demonstrated that being male was significantly associated with severe COVID-19. On the contrary, our study revealed females were associated with a 1.07-times increased risk of severe COVID-19 despite more males being hospitalized.…”
Section: Discussionmentioning
confidence: 99%